Pengaruh Politik Dalam Birokrasi Pemerintahan - Bambang Agus Diana (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2020)
Public Management is a management organization that is formed to achieve goals by coordinating the various interests of many people in a system and administrative pattern. So bureaucratic organizations are activities that require close coordination of activities involving a large number of people and are very structured in the process of implementing government. Increased bureaucracy must be supported by the people above who run the government and not only on the system, as well as any system or rules that are made, if only the people who run the system do not have the ability, and are consistent with their work or devices will be as expected. The public view, bureaucracy is closely related to the problem of service, orderly, systematic, both from the central government to the village level government. The real purpose of bureaucracy is that every public service need can be resolved quickly. Increasing government bureaucracy must be created through healthy apparatus both physically and spiritually (morality). The hope of the community for the bureaucracy is served well and quickly, without convolution with good service, it will accelerate the realization of the goals and aspirations of the people. Politics is an instrument for realizing community goals, namely through government bureaucracy, which results from the political process. The purpose of this paper is to provide a view of the political influence of reforming government bureaucracy. The conclusion is that if public services can be done well through government bureaucracy, then that must be the condition of the implementing government apparatus in addition to having human resources that are in accordance with a morally healthy body.